PEMANFAATAN FENOMENA ANGIN DARAT DAN ANGIN LAUT OLEH NELAYAN UNTUK MENCARI IKAN DI PANTAI PUGER KABUPATEN JEMBER - Anggraeni, Sisilia Nur Hikmah; Sudarti, Sudarti; Yushardi, Yushardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
One of the alternative energies on earth is wind. In the coastal area itself, it has been seen that fishermen are looking for fish in the sea using the wind as power to move their boats. The purpose of this study was to analyze the use of land and sea breezes by fishermen to find fish on Puger Beach, Jember Regency. This study uses methods in the form of field observations, direct interviews and taking sources from the literature. Fishermen will go to sea in the afternoon or evening using the sea breeze, and will arrive at sea in the morning using the land breeze. The condition of the coastal area is different when compared to areas far from the coast with the same hour conditions and the same weather. This difference can be seen from the temperature, wind speed and air pressure. The benefit of this research is as a source of knowledge for readers that physical theories from nature have been applied correctly by humans.